Effect of Ballistic Exercises in Explosive Capacity, Accuracy of Service and Spike of the Volleyball of the Physically Disabled-Sitting - Ammar Khaleel Ebrahim Al-Ezzi (Journal of Global Pharma Technology, 2016)
The study aimed to: Identify the effect of ballistic exercises in the explosive ability, accuracy of service and the spike of the volleyball of the physically disabled - sitting. The researcher used the experimental method in the style of the two equal groups. The research society was determined by the players of the national team in the 12-player volleyball team. They were divided into two equal groups (control and experimental). Ballistic exercises included moderate and moderate exercises similar to the skill performance, the course lasted for (8) weeks by (3) training units per week and the main findings of the researcher after the extraction of the results of Posttests the following conclusion:Ballistic training used has a positive effect on the development of exploding explosive capability, accuracy of service and spike of the ball off the disabled for movement-sitting.Keywords: Ballistic exercises, Explosive capacity, Accuracy and physically disabled.